Elevated hsCRP levels signal increased risk of future cardiovascular disease independent of lipid profile in H. pylori infection - Kansara, Gaurav Shashikant; Joshi, Pooja Nitin; Adhau, Shyam Rameshwar (International Journal of Research in Medical Sciences, 2017)
Background:There are reports that Helicobacter pylori (H. pylori) infection leads to changes in serum lipid profile and high sensitivity C-reactive protein (hsCRP) levels, but role of H. pylori in causing increased risk of cardiovascular disease remains a topic of debate. Methods:A case control study was conducted, in subjects without pre-existing atherosclerotic disease. We studied 72 otherwise healthy subjects in the age group of 20 to 60 years. All subjects underwent gastroduodenoscopy and H. pylori infection status was assessed by rapid urease test. Results:There were no statistical differences in serum total cholesterol, triglyceride, high density lipoprotein cholesterol, low density lipoprotein cholesterol levels or total cholesterol/HDL cholesterol ratios between cases and controls. However, serum hsCRP (high sensitivity C-reactive protein) levels were significantly higher in cases as compared to controls (P <0.05). Conclusion:The results of this study showed that H. pylori infection does not modify serum lipid levels; however, it leads to a rise in hsCRP, an important risk factor for atherosclerosis. It can be concluded that H. pylori infection may contribute to atherogenesis through the state of chronic inflammation, which is evidenced by elevated hsCRP levels.